Morphological diversity of foliar trichomes in Asteraceae from Sand-fields of the Pampa biome, Rio Grande do Sul State, Brazil - Liesenfeld,Vanessa (2019)
ABSTRACT Asteraceae is the largest family of angiosperms and occurs predominantly in grassland areas. This study aimed to identify and characterize the foliar trichomes of 34 Asteraceae species from Sand-fields of the Pampa biome, by means of epidermal analyzes (front and transverse view) under light and scanning electron microscopy. Eleven types of trichomes were identified and characterized: three glandular (recurved on the epidermis, erect-capitate and uniseriate to multiseriate vesicular-capitate) and eight non-glandular (simple conical, flagellate-filiform, aseptate-flagellate, whip-like, oblique-flagellate, branched with one arm, branched with two T-shaped arms, branched with three or more arms). The most representative glandular type was the uniseriate to multiseriate vesicular-capitate (58%) and the non-glandular type was the simple conical (35%). A large number of trichomes is an adaptive strategy to the adverse conditions of the Pampa biome and its morphological diversity can be useful in the family systematics.